Prolonged Hypoxia Induces Monocarboxylate Transporter-4 Expression in Mesenchymal Stem Cells Resulting in a Secretome that is Deleterious to Cardiovascular Repair. (24th March 2015) - Saraswati, Sarika; Guo, Yan; Atkinson, James; Young, Pampee P.
Abstract: MSCs encounter extended hypoxia in the wound microenvironment yet little is known about their adaptability to this prolonged hypoxic milieu. In this study, we evaluated the cellular and molecular response of MSCs in extended hypoxia (1% O2 ) versus normoxia (20% O2 ) culture. Prolonged hypoxia induced a switch toward anaerobic glycolysis transcriptome and a dramatic increase in the transcript and protein levels of monocarboxylate transporter-4 (MCT4) in MSCs. To clarify the impact of MCT4 upregulation on MSC biology, we generated MSCs which stably overexpressed MCT4 (MCT4-MSCs) at levels similar to wild-type MSCs following prolonged hypoxic culture. Consistent with its role to efflux lactate to maintain intracellular pH, MCT4-MSCs demonstrated reduced intracellular lactate. To explore the in vivo significance of MCT4 upregulation in MSC therapy, mice were injected intramuscularly following MI with control (GFP)-MSCs, MCT4-MSCs, or MSCs in which MCT4 expression was stably silenced (KDMCT4-MSCs). Overexpression of MCT4 worsened cardiac remodeling and cardiac function whereas silencing of MCT4 significantly improved cardiac function. MCT4-overexpressing MSC secretome induced reactive oxygen species-mediated cardiomyocyte but not fibroblast apoptosis in vitro and in vivo; lactate alone recapitulated the effects of the MCT4-MSC secretome. Our findings suggest that lactate extruded by MCT4-overexpressing MSCs preferentially induced cell death in cardiomyocytes but not in fibroblasts, leading ultimately to a decline in cardiac function and increased scar size. A better understanding of stem cells response to prolonged hypoxic stress and the resultant stem cell-myocyte/fibroblast cross-talk is necessary to optimize MSC-based therapy for cardiac regeneration. Stem Cells 2015;33:1333–1344